2021
DOI: 10.1136/bmjopen-2021-052008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of difference in postpartum depression among caesarean and vaginally delivered women at 6-week follow-up in hospitals in Pune District, India: an observational cohort study

Abstract: ObjectivesTo compare the proportion of postpartum depression at 6 weeks among women who had caesarean delivery and women who had vaginal delivery and to assess its association with some sociodemographic factors.DesignThis is a descriptive comparative study with prospective enrolment. We followed the enrolled women and assessed them for postpartum depression 6 weeks after delivery.SettingWe conducted the study in Pune District, India from July 2017 to December 2018. The study sites were all non-teaching governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[ 29 ] According to a study conducted in Pune, PPD is more likely in women, who had cesarean births and mothers, who were under the age of 25. [ 32 ] The National Family Health Survey (NFHS)-5 [ 33 ] shows that C-section delivery trends are increasing in India compared with NFHS-4. It may substantially increase the prevalence of PPD.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] According to a study conducted in Pune, PPD is more likely in women, who had cesarean births and mothers, who were under the age of 25. [ 32 ] The National Family Health Survey (NFHS)-5 [ 33 ] shows that C-section delivery trends are increasing in India compared with NFHS-4. It may substantially increase the prevalence of PPD.…”
Section: Resultsmentioning
confidence: 99%
“…These varied differences in the rate may also be due to differences in protocols for CS or different study participants and sample size. A study showed higher Postpartum Depression (PPD) rates in cesarean (33) sections than vaginal deliveries .…”
Section: (24)mentioning
confidence: 99%
“…For this reason, it is clear that (at first) AAPT is only possible when the fetus has left the maternal womb through a cesarean. Every cesarean comes with accompanying maternal health risks, physical as well as mental ( 18 , 19 ). Moreover, a cesarean comes with increasing risks in eventual subsequent pregnancies ( 18 ).…”
Section: Ethical Development Of Aapt Toward the First In-human Trialmentioning
confidence: 99%